Exploring Social Problems in Tobago - Sharon Campbell-Phillips (Budapest International Research and Critics University, 2020)
In Trinidad and Tobago, crime is escalating among our youths. These youths are teenagers who should be in school acquiring an education. Teenage crime is a name given to the crimes that are committed by people who are under the age of eighteen (18). In Trinidad and Tobago, most of the violent crimes are committed by children under the age of eighteen, who are either in school or have dropped out. Crimes committed mostly by teenagers include theft, assaults on other teenagers, gang violence, and even murder. Some of these juveniles are before the court defending themselves against crimes that they have committed, while others are in prison serving their sentences. Many of our youths are giving into social problems and neglecting the importance of their deviant behaviours. Social problem is a global epidemic that is affecting persons from all background, culture, race, age and belief. There have been patterns of negative behaviours among students in Tobago and it is becoming uncontrollable. Therefore, the aim of this study is to acquire information that can be used to help curb those unacceptable behaviours. Questionnaires were the method used and they were administered throughout the island of Tobago to persons belonging to different age groups. Based on the information gather and the findings, recommendations were suggested as a way of building better communities and a better Tobago. The purpose of this study is to explore social problems within Tobago and to identify the ways in which the youths are affected and by extension, the communities.